Doktryna prawna Abula Ala Maududiego - Jońca, Michał (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2018)
This article contains a description of the most important assumptions of the legal doctrine of a widely unknown thesis in Poland, the one by Abol Al Maududi – a very influential Pakistani theologian and lawyer. In the first place, the author presents the Maududi’s vision of Muslim law. Then he analyzes the principle of Allah’s exclusive sovereignty and its most important attributes. Subsequently, the issues of the sources of Islamic law are discussed, with particular reference to the Koran and Sunnah, the concept of faith (iman), deviation from it (kufr) and independent legal reasoning (ijtihad). At the end, the concept of jihad is analyzed, which Abul Ala Maududi devoted attention to in one of his most famous works
Keywords: islam; Maudoodi, Syed Abul'Ala (1903-1979); Sharia; Islamic law; ijtihad; jihad; fundamentalism